Association between obesity and sleep disorders in primary school children: a cross-sectional study (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND The prevalence of obesity in primary school children in Jakarta has reached 14% in 2013. Among many disorders, obesity can cause sleep disorders. However, sleep disorders in children are often overlooked by parents, even though they can cause physical, social, and psychological impacts. Therefore, it is necessary to find the association between obesity and sleep disorders in primary school children. METHODS This cross-sectional study was performed between July-September 2015 on 107 children attending Menteng 01 Primary School, Jakarta. Children's weight and height were measured and then their parents filled out the brief infant sleep questionnaire (BISQ). The collected data were analyzed using chi-square. RESULTS In this study, 20.6% of the children were obese, which was higher than the prevalence of obesity in Jakarta. Meanwhile, sleep disorders occurred in 62.6% of children. Data about children's sleep habits and parents' opinion about their children's sleep were obtained. It showed that snoring and parents' opinion about sleep disorders were factors associated with children's sleep disorder. Statistical analysis also showed a significant association between obesity and sleep disorders in children (p = 0.037). CONCLUSIONS The incidence of obesity in primary school children is high and is associated with sleep disorders.